Hand posture for beginner piano playing using plush toy assisted learning / Shugeshini Kumanan - Shugeshini , Kumanan (2020)
This research paper explored the possibilities of using an animal plush toy as a tool to teach piano playing hand posture among participants formed by children age four up to six years old. The idea of Plush Toy Assisted Learning (PTAL) originates from AAL or animal assisted learning. Adopting a case study that involved a quantitative and a qualitative research framework, this research reveals an in-depth observation of a proposed new pedagogical idea in developing a proper hand posture using an animal soft toy as a tool towards children. Methodology includes a self-reflexive account of the researcher as a teacher via participant-observation, audit trail, log book, video recording, interaction between the child and the plush toy, comparison by interest and also the effectiveness of teaching approaches with or without the animal plush toy. The outcome shows that PTAL would be effective for younger children who are beginner piano player to learn their piano playing hand postures. This includes the duration of the process of learning and the effectiveness in applying the animal plush toy in replacing real-animal assisted learning to play the piano using a proper hand posture. Traits of pattern of \learning and also behavioural response in children towards the plush toy were discussed.